Improving Resiliency and Patient Satisfaction in a Rural Community Hospital - Taylor, Melinda (My University, 2022)
The lack of resiliency affects the overall well-being of healthcare professionals (HCP) negatively impacting one’s ability to provide compassionate, safe, quality care. The literature supports that lack of resiliency contributes to burnout and compassion fatigue but could be corrected with self-care practices. Organizations providing stress management and resiliency training (SMART) and mindfulness resources fulfill the Institute for Healthcare Improvement’s quadruple aim while meeting Healthy People 2030 goals and objectives. However, resiliency studies lack population diversity and correlations with patient satisfaction. This quasi-experimental Doctor in Nursing Practice project aimed to provide education and mindfulness resources to enhance resiliency with healthcare professionals while improving patient satisfaction in a rural community hospital located in Eastern North Carolina. The sample size was 36 HCPs from the Emergency Department. SMART education and a restorative space were provided and studied over eight weeks. Resiliency measures included: the 14-item resilience scale (RS14), pre- and post- project, and continuum scale to evaluate restorative space efficacy. Patient satisfaction was tracked through the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) reports. Project outcomes and evaluations suggest that education and restorative space significantly enhanced resiliency and improved patient satisfaction. Further high-quality, robust studies should be done with healthcare professionals using an array of resiliency interventions to evaluate the efficacy and the implications with patient satisfaction to improve outcomes and enhance nursing practice.
Keywords: nurse, resiliency, healthcare professional, quadruple aim, patient satisfaction, mindfulness training, health promotion, resiliency/stress reduction programs, relaxation rooms